Enterprise Systems Modeling: the ERP5 Development Process - Monnerat, Rafael Manhaes; Carvalho, Rogerio Atem de; Campos, Renato de [UNESP]; ACM (Assoc Computing Machinery, 2008)
The design and implementation of an ERP system involves capturing the information necessary for implementing the system's structure and behavior that support enterprise management. This process should start on the enterprise modeling level and finish at the coding level, going down through different abstraction layers. For the case of Free/Open Source ERP, the lack of proper modeling methods and tools jeopardizes the advantages of source code availability. Moreover, the distributed, decentralized decision-making, and source-code driven development culture of open source communities, generally doesn't rely on methods for modeling the higher abstraction levels necessary for an ERP solution. The aim of this paper is to present a model driven development process for the open source ERP ERP5. The proposed process covers the different abstraction levels involved, taking into account well established standards and common practices, as well as new approaches, by supplying Enterprise, Requirements, Analysis, Design, and Implementation workflows.
Keywords: ERP; Enterprise Informaton Systems; GERAM